Strategic Market Planning / Problems and Analytical Approaches - Abell F. Derek; Hammond S. John (Prentice Hall, 1979)
Analytical Prerequisites for Strategic Planning ,The Nature of Strategic Market Planning, Analyzing Market Opportunity and Assessing Company Capability, Cost Dynamics: Scale and Experience Effects, Formal Strategic Planning Methods, Portofolio Analysis, Market Attractiveness and Business Position Assessment, The Use of Pooled Business Experience: The Pims Project, The Formal Methods Compared, Creative and Managerial Aspects of Planning, Defining the Business and Making Bridges to othe Strategic Decisions, The Human Side of Planning, Preparing a Strategic Market Plan, Index of Text.
Analytical Prerequisites for Strategic Planning ,The Nature of Strategic Market Planning, Analyzing Market Opportunity and Assessing Company Capability, Cost Dynamics: Scale and Experience Effects, Formal Strategic Planning Methods, Portofolio Analysis, Market Attractiveness and Business Position Assessment, The Use of Pooled Business Experience: The Pims Project, The Formal Methods Compared, Creative and Managerial Aspects of Planning, Defining the Business and Making Bridges to othe Strategic Decisions, The Human Side of Planning, Preparing a Strategic Market Plan, Index of Text.